Jardim Miriam Arte Clube: lugar de encontro entre arte e direitos humanos - Ribas, Luciano do Monte (2010)
This work relates, within the context of globalization, contemporary art with human rights, taking as a case study on the experience of the artist Monica Nador in to Miriam Garden Art Club (Jamac), a nongovernmental organization headquartered in São Paulo. Divided into three chapters, this study aims at first, to characterize the object studied and demonstrate that the right to access, know, understand and make art to be understood as part of human rights. Below, defines the processes of globalization, localization, hegemony and counter-hegemony, inserting the Jamac this context. In the final chapter, defines four generations of human rights, identifies discourses they share with contemporary art and discusses how Miriam Garden Art Club, by exercising the transformative power of artistic activity, is able to promote art as a human right.